The sinusoidal probe: a new approach to improve electrode longevity - Sohal, Harbaljit S.; Jackson, Andrew; Jackson, Richard; Clowry, Gavin J.; Vassilevski, Konstantin; O’Neill, Anthony; Baker, Stuart N. (Frontiers in Neuroengineering, 2014)
Micromotion between the brain and implanted electrodes is a major contributor to the failure of invasive Brain-Machine Interfaces. Movements of the electrode tip cause recording instabilities while spike amplitudes decline over the weeks/months post-implantation due to glial cell activation caused by sustained mechanical trauma. We have designed a sinusoidal probe in order to reduce movement of the recording tip relative to the surrounding neural tissue. The probe was microfabricated from flexible materials and incorporated a sinusoidal shaft to minimize tethering forces and a 3D spheroid tip to anchor the recording site within the brain. Compared to standard microwire electrodes, the signal-to-noise ratio and local field potential power of sinusoidal probe recordings from rabbits was more stable across recording periods up to 678 days. Histological quantification of microglia and astrocytes showed reduced neuronal tissue damage especially for the tip region between 6-24 months post-implantation. We suggest that the micromotion-reducing measures incorporated into our design decreased the magnitude of gliosis, resulting in enhanced longevity of recording.